Primary care clinicians’ perceptions of colorectal cancer screening tests for older adults - Park, Reuben (Prev Med Rep, 2021)
Colonoscopy is an effective screening test for colorectal cancer but is associated with significant risks and burdens, especially in older adults. Stool tests, which are more convenient, more accessible, and less invasive, can be important tools to improve screening. How clinicians make decisions about colonoscopy versus stool tests in older patients is not well-understood. We conducted semi-structured interviews with primary care clinicians throughout Maryland in 2018–2019 to examine how clinicians considered the use of stool tests for colorectal cancer screening in their older patients. Thirty clinicians from 21 clinics participated. The mean clinician age was 48.2 years. The majority were physicians (24/30) and women (16/30). Four major themes were identified using qualitative content analysis: (1) Stool test equivalency - although many clinicians still considered colonoscopy as the test of choice, some clinicians considered stool tests equivalent options for screening. (2) Reasons for recommending stool tests – clinicians reported preferentially using stool tests in sicker/older patients or patients who declined colonoscopy. (3) Stool test overuse – some clinicians reported recommending stool tests for patients for whom guidelines do not recommend any screening. (4) Barriers to use – perceived barriers to using stool tests included lack of familiarity, un-returned stool test kits, concern for accuracy, and concern about cost. In summary, clinicians reported preferentially using stool tests in sicker and older patients and mentioned examples of potential overuse. Additional studies are needed on how to better individualize the use of different colorectal screening tests in older patients.